Effect of transformational leadership, institutional quality and political competition on corporate performance of Nigeria National Petroleum Corporation - Ugochukwu, Osuagwu Justine (2019)
Corporate performance is now widely recognized as the cause of organizational failure. Both academia and practitioners claim that corporate performance is under researched. One of the corporate performance challenges facing NNPC is red tape, which imposes additional costs to the corporate. The aim of the study to examine the basic corporate performance challenges hindering NNPC in its attainment of organizational goals. This study addresses the issue on corporate performance by proposing mediators for transformational leadership; institutional quality and political competition; as possible factors that may affect corporate performance. This study then examines interrelationships between transformational leadership, institutional quality and political competition on corporate performance. This is a quantitative study. Three hundred and seventy questionnaires were distributed to employees of NNPC holding leadership position and 261 completed questionnaires were returned. The data was analyzed using regression model and Partial Least Squares Structural Equation Modeling Techniques (PLS-SEM), and Smart PLS version 3.0 was the software used to run the analysis. The study revealed that transformational leadership style directly influences corporate performance significantly, while institutional quality and political competition did not mediate the relationship between transformational leadership and corporate performance. However, institutional quality and political competition have direct positive and negative effect on corporate performance. In this study, there was no direct relationship between transformational leadership and institution quality as well as political competition but transformational leadership, institution quality and political competition have significant effect on corporate performance independently. The study found that the adoption of transformational leadership style and favorable political competitiveness are strategies of improving NNPC performance while institutional quality should be implemented if desirable performance of NNPC is expected in Nigeria.